A gas flow model for layered landfills with vertical extraction wells. (August 2017) - Feng, Shi-Jin; Zheng, Qi-Teng; Xie, Hai-Jian
Highlights: Develop a 2D analytical model for LFG flow in layered landfills with vertical wells. Study effects of different well boundary conditions and LFG extraction systems. Explore a dimensionless double-layer system (a cover and a waste layer). Quantitatively characterize effects of 7 variables and integrate them into 3 ones. Abstract: This paper developed a two-dimensional axisymmetric analytical model for layered landfills with vertical wells. The model uses a horizontal layered structure to describe the waste non-homogeneity with depth in gas generation, permeability and temperature. The governing equations in the cylindrical coordinate system were transformed to dimensionless forms and solved using a method of eigenfunction expansion. After verification, the effects of different well boundary conditions and gas extraction systems on recovery efficiency were investigated. A dimensionless double-layer system, consisting of a cover and a waste layer, was also explored. The results show that a constant vacuum pressure boundary condition can be enough to describe a perforated pipe surrounded by drainage gravel with a reasonable value of well radius, such as half the radius of gravel fill. Also, the 7 independent variables (one marked with an asterisk is dimensionless) of a double-layer system can be integrated into 3 dimensionless ones: Cover permeability K v1 ∗ /(Vertical gas permeability of waste K v2 ∗  × Cover thickness h 1 ∗ ),  − Vacuum pressure p w  ×  P atm K v2 ∗ /( μR g T 2  × Gas generation rate of waste s 2 ) and ln(Well radius r w ∗ )/(Anisotropy degree of waste k 2 ∗ ). The integration is based on the inherent mechanism of this flow system with certain simplification. The effects of these variables are then quantitatively characterized for a better understanding of gas recovery efficiency. Same recovery efficiency can be achieved with different variable combinations. For example, increasing h 1 ∗ (such as doubling it) has the same effect with decreasing K v1 ∗ (such as halving it). Along with the reduction of variables by half, the integration can facilitate the preliminary design, and is a small but important advance in the consideration of MSW non-homogeneity.